The Impact of Artificial Intelligence on Institutional Performance: The Variable of the Intellectual Capital Broker in Commercial Banks operating in the Kingdom of Saudi Arabia (The International Journal for Scientific Research, 2024)
The aim of this study was to investigate the impact of artificial intelligence (AI) with its dimensions (expert systems, automatic machine learning, usability) on organizational performance, mediated by intellectual capital, in commercial banks operating in the Kingdom of Saudi Arabia. The study population comprised all employees in commercial banks in Saudi Arabia, and the study relied on a proportionate stratified random sample of administrators in these banks (managers, department heads, supervisors, administrators), totaling 338 administrators. The study utilized a descriptive-analytical methodology, developing a questionnaire consisting of 38 items. Statistical Package for the Social Sciences (SPSS) was used for data analysis and hypothesis testing. The study yielded several key findings: There is a significant impact of artificial intelligence, with its dimensions (expert systems, automatic machine learning, usability), on organizational performance. Additionally, there is a significant impact of artificial intelligence dimensions on intellectual capital, and intellectual capital significantly impacts organizational performance. Moreover, there is a significant indirect impact of artificial intelligence dimensions on organizational performance through intellectual capital in commercial banks. The study recommended that bank management focus on expert systems provided by artificial intelligence to acquire knowledge from stored databases for problem-solving and application through organizational performance and intellectual capital. It also suggested developing systems to logically and programmatically address accounting errors to enhance the ability to automatically monitor and reevaluate internal processes continuously in line with changes in the external work environment. This can be achieved through the use of modern technology, knowledge transfer, research, and development.
Keywords: Artificial Intelligence; Organizational Performance; Intellectual Capital; Commercial Banks in the Kingdom of Saudi Arabia